Coastline changes under natural and anthropogenic drivers in a macro-tidal estuary between 2000-2020 - Wang, Qian; Ma, Ye; Cheng, Zhixin; Du, Yixiao (Frontiers in Marine Science, 2023)
Coastline changes in estuarine areas can result from a combination of natural processes such as erosion, sedimentation, and sea-level rise, as well as human activities, including urbanization and infrastructure development. These changes have the potential to affect the local environment, including submarine groundwater discharge, wetlands, and navigation routes. The Yalu River Estuary (YRE), situated on the border between China and North Korea, has been experiencing significant changes in its coastline over recent years. This study aims to investigate the coastline dynamics in the YRE from 2000 to 2020. The study employs Landsat 5/7/8 satellite data and proposes a modified Normalized Difference Water Index (NDWI) to accurately delineate the coast boundary, particularly in areas with extensive tidal flats like the YRE. The research findings indicate that from 2010 to 2020, significant changes occurred in the YRE shoreline, with erosion being the dominant trend. Human activities and alternations in hydrological conditions are important factors affecting the YRE coastline changes, contributing to the formation of distinctive spatiotemporal patterns. An extreme flooding event in the year 2010 also altered the inner estuarine coastline in the YRE, indicating the impact of strong natural drivers. Findings from this study provide a comprehensive understanding of the evolving coastal environment, considering natural and anthropogenic drivers, and highlight the importance of continuous monitoring in a region of ecological and geopolitical significance.